2015
DOI: 10.20533/ijcdse.2042.6364.2015.0300
|View full text |Cite
|
Sign up to set email alerts
|

Netspeak and a Breach of Formality: Informalization and Fossilization of Errors in Writing among ESL and EFL Learners

Abstract: Abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 14 publications
(28 reference statements)
1
3
0
Order By: Relevance
“…As per 15 participants Sms English in future will spread and develop; as per 9 participants, it will replace or mix with or become a part of Standard English and as per 6 participants, it will remain as means of communication. The results of this study concurs with Aljaraideh and Al Bataineh (2019), Shaari & Bataineh (2015), Njemanze, (2012), Ping, A. C. et al (2011), Geertsema et al (2011), Winzker et al (2009Winzker et al ( ), O"connor (2006…”
Section: Overall Findingssupporting
confidence: 91%
See 1 more Smart Citation
“…As per 15 participants Sms English in future will spread and develop; as per 9 participants, it will replace or mix with or become a part of Standard English and as per 6 participants, it will remain as means of communication. The results of this study concurs with Aljaraideh and Al Bataineh (2019), Shaari & Bataineh (2015), Njemanze, (2012), Ping, A. C. et al (2011), Geertsema et al (2011), Winzker et al (2009Winzker et al ( ), O"connor (2006…”
Section: Overall Findingssupporting
confidence: 91%
“…Another study by Winzker et al (2009) indicated that sms English have a great influence on student"s writing performance. Likewise, Shaari & Bataineh (2015) stated that online language hinders the entire process of English language acquisition and learning. With the enormous exposure to online language, EFL students may believe this as something normal or perhaps confusing.…”
Section: Introductionmentioning
confidence: 99%
“…As shown in Table 1, smartphone (90.4%) was used by the majority of the students for their distance learning experience, followed by laptop (31.6%), personal computer (15.5%), and tablet (5.3%), respectively. Smartphone is widely used among university students in Jordan where the Internet is available in affordable cost and online social media is the primary platform for the university students that replaces the traditional means such as TV and Radio (Azianura & Khaleel, 2015).…”
Section: Population Research Sample and Sample Characteristicsmentioning
confidence: 99%
“…Extensive interviews are required with decided on University students who locate that a few private facts, consisting of emotions and attitudes, can't be measured with the aid of using textual content alone. Shaari & Bataineh (2015):…”
Section: Research Procedures For the Studymentioning
confidence: 99%